Using your profanisaurus: Comparisons, analogies and cultural capital in two English Literature seminars. (February 2013) - Bruce, Susan
'Using your profanisaurus' derives from a project, The Production of University English, whose earliest findings were published in Arts and Humanities in Higher Education in 2005. By analysing 'ordinary' discussions in 'ordinary' English Literature classes in diverse universities, the project seeks to uncover what really happens when English is taught and learned in British Higher Education. This article examines two instances where students compare the text they are studying with another artifact, in order to raise questions about canonicity, culture, and the act of comparison itself. The project also aims to show how analytical methods generated from the discipline of English may be employed to elucidate other texts, including the 'text of the classroom'. Consequently, the article begins with a discussion of three artifacts whose form presupposes a comparative reading.